China’s Policy in Arctic region - V. Yu. Karandasheva (Проблемы постсоветского пространства)
The article deals with the process of formation of China’s Arctic policy and mechanisms for its implementation. Till the end of the 1990s, Beijing was not interested in the Arctic region because of its geographical remoteness from China, as well as because of the lack of the necessary scientific and technological basis. The economic reforms of 1972 and the establishment of the Arctic Council in 1996 gave an impetus to the development of China’s policy in the Arctic. Since then, China has intensified its activities aimed at expanding the state’s presence in the region. Special attention is given to China’s policy document in the region ― a white paper titled “China’s Arctic Policy”. It is noted that this document was aimed at legitimizing China’s activities in the region.Despite the fact that the Arctic is not a priority region for Beijing, China is a prominent actor there. China’s attention to the Arctic is determined by economic factors, namely, by the possible development of the region’s resources, as well as its transport capacities, which can be used in the framework of the One Belt One Road Initiative.The article analyses China’s cooperation with the «Arctic five» countries and the position of the Arctic States towards intensifying Beijing’s activities in the region. China is promoting cooperation with Norway, Denmark and Iceland. despite the existing contradictions, it is noted that the Arctic states are interested, as Chinese investments play an important role in the development of the region. China has consistently stated the need for greater involvement of interested non-regional states in the multilateral management of the region, while respecting the sovereignty of the Arctic countries.